Extraction Yield, Phytochemicals Analysis, and Certain in Vitro Biological Activities of Artemisia Herba Alba Extracts - Benmeziane, Siham; Saleh Haddadin, Malik; Abdullah Al-Domi, Hayder (Jordan Journal of Agricultural Sciences, 2023)
The objectives of this study were to determine the extraction yield and phytochemical composition of different Artemisia herba alba (AHA) extracts, as well as to investigate in vitro their antioxidant, anti-inflammatory, anti-glycation, and antibacterial activities, also to study the effect of the solvent extraction on these characteristics. Four solvents with different polarities were used to prepare AHA extracts. Several in vitro tests were used in this study to evaluate the extract yield and phytochemical characteristics of the different AHA extracts, as well as to determine certain of their biological activities. Our findings showed that 80% aqueous ethanolic extract, significantly compared to other extracts, exhibited higher extraction yield (15.3%), higher phytochemical content (263.93 mg GAE/g E for total phenols), (40.94 mg QE /g E for total flavonoids), and (35.99 mg GAE/g E for total tannins), and higher Diphenyl-2-Picrylhydrazyl (DPPH) radical scavenging capacity (IC50= 4.13 mg/mL) with no significant differences when compared to methanolic extract, as well as higher anti-glycation activity (IC50= 3.96 mg/mL). However, the methanolic extract had a significant inhibitory effect against the majority of the tested bacteria compared to other extracts. While the anti-inflammatory potential of distilled water extract was significantly higher (IC50= 2.96 mg/mL) compared to another extract. It is clear that the solvent type had a significant effect on the chemical and biological characteristics of AHA. The diversity and significance of Artemisia herba alba’s biological activities demonstrate its potential application in the pharmaceutical and food fields.